Satellite tagging confirms long distance movement and fast dispersal of Patagonian toothfish (Dissostichus eleginoides) in the Southwest Atlantic - Kim, Eunjung; Lam, Chi Hin; Park, Gyum Joon; Lee, Jong Hee (Frontiers in Marine Science, 2024)
Introduction To better understand Patagonian toothfish (Dissostichus eleginoides) movement and habitat in the Southwest Atlantic, fifty popup satellite archival tags (PSATs) were deployed off Davis Bank on North Scotia Ridge between 2019 and 2020 on individuals ranging from 97-139 cm total length. Methods PSATs (18 Lotek Wireless PSATFLEX and 32 Wildlife Computers MiniPAT) were programmed to detach after completing 1 to 16-month missions recording pressure (depth) and water temperature. Results Six tags failed to report, and among the remaining 44 reporting tags, 34 reported on schedule, up to 487 days at sea – the longest electronic tag deployment for this species to date. Although the majority of PSATs reported within 50 km from the release sites, confirming high site fidelity, 12% of tags reported more than 200 km away, showing connectivity to Shag Rocks and South Georgia in the Southern Ocean. Toothfish moved across the Antarctic Polar Front through/to areas with no fishing activities, and hence, explained the absence of any previous conventional tag recapture. A 1-month transit to the Falkland/Malvinas Plateau Basin also revealed that toothfish can attain a surprisingly high movement rate of 33 km day-1. Discussion Fishery independent examples of toothfish presence and their movement capabilities are inviting us to broaden our examination on how toothfish move around their Scotia Arc habitats and link up different regional aggregation sites in the South Atlantic.